The Metabolic Sensor GPR43 Receptor Plays a Role in the Control of Klebsiella pneumoniae Infection in the Lung - Galvão, Izabela; Tavares, Luciana P.; Corrêa, Renan O.; Fachi, José Luís; Rocha, Vitor Melo; Rungue, Marcela; Garcia, Cristiana C.; Cassali, Geovanni; Ferreira, Caroline M.; Martins, Flaviano S.; Oliveira, Sergio C.; Mackay, Charles R.; et al. (Frontiers in Immunology, 2018)
Pneumonia is one of the leading causes of death and mortality worldwide. The inflammatory responses that follow respiratory infections are protective leading to pathogen clearance but can also be deleterious if unregulated. The microbiota is known to be an important protective barrier against infections, mediating both direct inhibitory effects against the potential pathogen and also regulating the immune responses contributing to a proper clearance of the pathogen and return to homeostasis. GPR43 is one receptor for acetate, a microbiota metabolite shown to induce and to regulate important immune functions. Here we addressed the role of GPR43 signaling during pulmonary bacterial infections. We have shown for the first time that the absence of GPR43 leads to increased susceptibility to Klebsiella pneumoniae infection, which was associated to both uncontrolled proliferation of bacteria and to increased inflammatory response. Mechanistically, we showed that GPR43 expression especially in neutrophils and alveolar macrophages is important for bacterial phagocytosis and killing. In addition, treatment with the GPR43 ligand, acetate, is protective during bacterial lung infection. This was associated to reduction in the number of bacteria in the airways and to the control of the inflammatory responses. Altogether, GPR43 plays an important role in the “gut-lung axis” as a sensor of the host gut microbiota activity through acetate binding promoting a proper immune response in the lungs.